(untitled) - Jackson, Cecil Wilfrid (Boston, 2015)
The text provides students a thorough overview of the most frequently used methods of overstating earnings and assets or understating debt in financial statements. It also provides detailed coverage of the main signals indicating possible fictitious reporting in financial statements to help students learn what to look for. And because breakdowns in ethics underlie accounting fraud, the text presents three major theories of ethics, plus applicable ethical decision-making models as well as opportunities for students to apply ethical models to real-world situations.
Keywords: Gian lận kế toán,Accounting fraud; Hoa Kỳ,United States